Digital Technology Adoption Among Italian Farmers: An Extended Technology Acceptance Model Approach in the Horticultural Sector - Elena Cozzi; Davide Menozzi; Giulia Maesano; Maurizio Canavari; Cristina Mora (Bio-based and Applied Economics, 2025)
The adoption of digital technologies in agriculture is essential for enhancing sustainability, productivity, and resource efficiency. This study investigates the factors influencing Italian horticultural farmers' adoption of innovative water-smart agricultural technologies using an extended Technology Acceptance Model (TAM3). The research employs a structured survey conducted with 251 Italian farmers, analysing their perceptions of technology usefulness, ease of use, social norms, and sustainability outcomes. Structural equation modelling (SEM) confirms that perceived usefulness significantly influences adoption intentions, while perceived ease of use plays a limited role. Social norms and sustainability-related benefits also emerge as critical determinants. Results also indicate the impact of farm size and workforce on adoption behaviour. These findings highlight the need for targeted policies, training programs, and financial incentives to overcome adoption barriers. The study provides insights for policymakers, technology developers, and agricultural stakeholders to foster digital innovation in the horticultural sector, contributing to sustainable water management practices.